Skin imaging in systemic sclerosis - Kang, Taeyoung (Eur J Rheumatol, 2014)
Fibrotic involvement of the skin is a cardinal feature of systemic sclerosis (SSc). The extent of skin involvement is associated with internal organ involvement, coinciding with more severe disease course and poor prognosis. A palpation-based semi-quantitative score, the modified Rodnan skin score, is widely used for the assessment of skin involvement, but it is entailed by significant limitations. More objective approaches to measure skin involvement employing imaging have been explored continuously in the past decades and are currently advancing. Here, we review the use of different imaging techniques for the assessment of skin involvement in patients with SSc, focusing mainly on ultrasound, magnetic resonance imaging, and optical coherence tomography.